Penelitian Agama di Indonesia Perspektif Mukti Ali - Shofiyah, Nida; Zulkarnain, Iskandar (Hadara : Journal of Da'wah and Islamic Civilization, 2025)
The purpose of this study is to analyze religious research in Indonesia from Mukti Ali's perspective. The description research method is a suitable method to be applied in religious research. Based on the research results, religious research offered by Mukti Ali in his book Religious Research in Indonesia can make a major contribution to the development of Islam, especially Islamic education. A proper understanding of Islam as a whole can provide a broad insight into how to become an ideal Islamic educator. So that he can position himself according to the situation and conditions at hand. A broad understanding of an educator can shape him into an ideal Muslim so that the goals of Islamic education are well achieved. Thus, it is clear that if religious research is carried out properly and uses the right research methods, it can make a major contribution or contribution to various fields, be it social, cultural, political, economic, or educational.